2004
DOI: 10.1039/b403982c
|View full text |Cite
|
Sign up to set email alerts
|

Transport and reaction in microscale segmented gas–liquid flow

Abstract: We use micro particle image velocimetry (microPIV) and fluorescence microscopy techniques to characterize microscale segmented gas-liquid flow at low superficial velocities relevant for chemical reactions with residence times of up to several minutes. Different gas-liquid microfluidic channel networks of rectangular cross section are fabricated in poly(dimethylsiloxane) (PDMS) using soft lithography techniques. The recirculation motion in the liquid segments associated with gas-liquid flows as well as the symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
394
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 489 publications
(407 citation statements)
references
References 41 publications
8
394
0
5
Order By: Relevance
“…Low axial mass transfer or back mixing occurs between two adjacent liquid slugs. Moreover, both radial mass and heat transfer can be intensified by internal circulation in the single slugs (Günther et al, 2004;Thulasidas et al, 1997). These merits make slug flow an ideal regime for improving the reaction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Low axial mass transfer or back mixing occurs between two adjacent liquid slugs. Moreover, both radial mass and heat transfer can be intensified by internal circulation in the single slugs (Günther et al, 2004;Thulasidas et al, 1997). These merits make slug flow an ideal regime for improving the reaction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Segmented flow can eliminate Taylor dispersion by localizing samples as aqueous droplets or plugs formed in a stream of water-immiscible carrier fluid. [22][23][24][25] A surge of recent research into segmented flows has shown the potential of this approach for chemical measurement. Droplets or plugs from femtoliter to microliter volume can be reproducibly created using a variety of microfluidic geometries including tee junctions, 26 Yjunctions, 23 The goal of this study was to combine in vivo microdialysis sampling with a segmented flow microfluidic device to conserve temporal resolution while sample plugs were transported from the probe to a downstream detection system.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Gas bubbles were used in liquid-gas twophase segmented flow as well. 25,26 For applications involving long arrays of plugs, two drawbacks may need to be overcome in using gas bubbles as spacers: (1) compressible gas bubbles could cause flow fluctuation and a lag in response to the change of flow rates in pressure-driven flow, and (2) gas bubbles may dissolve in the fluorinated carrier fluid under high pressure. 27 Solving these problems would be especially useful when performing screens using cartridges 28 preloaded with reagent plugs.…”
Section: Introductionmentioning
confidence: 99%